Directorates of the Ministry of Agrarian Reform Iraq in 1958 - 1968 (Journal of the College of Education for Women, 2019)
After the issuance of agrarian reform first law of 1958 events social economicaccelerating out of sync with political events on the application of the agrarian reform lawissued a government executive branch law number (74) in May 1959 was the introduction ofthe ministry of Agrarian reform and the development of a new system of the ministry ofagrarian reform and its department to determine structural ministry the new work starteddepartment of the ministry ptt.